Skyscraper cinema : architecture and gender in American film - Schleier, Merrill (University of Minnesota Press, 2009)
Whether tall office buildings, high-rise apartments, or lofty hotels, skyscrapers have been stars in American cinema since the silent era. Cinema's tall buildings have been variously represented as unbridled aspiration, dens of iniquity and eroticism, beacons of democracy, and well-oiled corporate machines. Considering their intriguing diversity, Merrill Schleier establishes and explains the impact of actual skyscrapers on America's ideologies about work, leisure, romance, sexual identity, and politics as seen in Hollywood movies. Schleier analyzes cinematic works in which skyscrapers are an i.